The effect of flexible working and job satisfaction on employee productivity at STIE GICI Depok - Evilina Sjaiful; Nurdin Rifai; Gena Prasetya Noor; Edityawati Indah Edityawati; Herman Susilo (International Journal of Applied Finance and Business Studies, 2026)
This study aims to analyze the influence of flexible working and job satisfaction on employee productivity at STIE GICI. The research method used is a quantitative approach with data collection techniques through questionnaires to employees. The research sample used saturated sampling techniques, so that the entire population was used as respondents. Data analysis was carried out using multiple linear regression with the help of SPSS. The results of the study showed that partially flexible working had a positive and significant effect on employee productivity with a t-count value of 8.496 and a significance of 0.000. Job satisfaction also has a positive and significant effect on employee productivity with a t-count value of 4.351 and a significance of 0.000. Simultaneously, both variables had a significant effect on productivity with an F-calculated value of 49.872. The determination coefficient value of 54.4% shows that flexible working and job satisfaction can explain employee productivity.